Mantik Aristotle dalam Karya Ulama: Satu Analisis Terhadap Beberapa Bahan Penulisan al-Imam Fakhr al-Din al-Razi (M. 606 H. / 1209 M.) - Hamat, Mohd Fauzi (Jurnal Usuluddin, 2000)
This article tries to elaborate the use and application of a type of methodology based on Aristotelian logic in literatured among some works by Fakhr al-Din al-Razi; a theologist and philosopher. A special discussion will be focused on his popular works in Theology as well as in Islamic Jurisprudence which are considered as two main branches of Islamic thought. The method of argumentation is used in according to the rule of logic will also be discussed in this article.